Artes de prevenir: educação e saúde pelas visitadoras sanitárias no Paraná (1920-1940) - Ristow, Márcia Regina (2011)
This survey aims to collect a written memory about the Health Councilor in Paraná, to show its trajectory encrusted in customs and administrative rationalities in education and public health, to describe a time when the costumes were alongside the disciplinary order, as well as describe the creation of social roles for Health Councilor in the State of Paraná through 1920-1940. To do this historic survey and delimit the trajectory and the time clipping, we got Reports of Government, Statistical Reports of Demographer Health of Paraná as search report sources, editions of the magazine Revista Médica do Paraná , Travel Reports of Inspectors in Education and Health, documents from the Archive of Medicine College of the State and the reports of the National Department of Health about the organization of Health Districts of the State. We try to show the work that had already being developed by laymen in health in the countryside of the State. With policies to achieve the countryside and effective occupation of the territory, this attendance used to be the only way of medical practicing. So far, this practical service represented one of the unique alternatives to expand ideals of health and sanitarism that had being drawn up by the Government and facing a discourse of modernity of Brazil. The jobs of this layman were incorporated into the policies to take health to the countryside as well as school care policies. This professional then was regimented by the health structure that is proposed for this season, particularly in the Sanitary Districts. Its area of action was extended also to home visits, help to doctors, school visits, to patients, and in the factories. This practice of care and dissemination of the prophylactic ideals and health was placed to this character, sometimes excluded from science by its mystical features, sometimes incorporated for it, and marked as unique agent of support towards the communities of the countryside to establish the ideals of a medical science that sometimes condemned it. In the late 1940, we see social roles already refurbished and delimited by a legal-administrative planning. Its "place" was enclosed within the institutions and with pre-established chores